Incremental Dynamic Analysis of Infilled Frames with Open Ground Floor - Todorov, Koce; Lazarov, Ljupco (European Association of Earthquake Engineering (EAEE), 2018)
Reinforced concrete frames with masonry infill are often used structural systems throughout the world, especially in developing countries and countries around Mediterranean region. Irregular distribution of infill in plane and along building height can lead to series of unfavourable effects (torsion effects, dangerous collapse mechanisms, soft or weak storey, variations in the vibration period, etc.). In order to investigate the influence of irregular distribution of masonry infill to the seismic performance of code designed reinforced concrete frames, an extensive nonlinear dynamic analysis was performed. Six reinforced concrete frames with different number of storey, designed as bare frames were analysed. In the phase of assessment, all structures were upgraded with the masonry infill panels in all storeys except the first one. Masonry infill was defined with two different strength and stiffness characteristics. All frames were exposed to twenty-one different earthquake ground motions scaled to ten different amplitudes. In the case of low rise buildings, the presence of infill is usually unfavourable for all levels of PGA, leading to the formation of soft storey mechanism. In the case of midrise buildings, the presence of infill reduces the seismic demand up to the PGA of 0.3g. At high rise buildings distribution of damage depend on the mechanical characteristics of infill as well as the frequency content of input ground motion. The ratio between maximal interstorey drift and maximal top drift can be a good indicator of damage distribution thru the building height. In order to quantify this relationship, regardless of the number of storey, the parameter named as index for distribution of displacement at height (DDH) was defined.
Keywords: incremental dynamic analysis; masonry infill; open ground floor; damage distribution